1983
DOI: 10.1093/ije/12.2.185
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Smoking during Adolescence—The MRC/Derbyshire Smoking Study

Abstract: Each year from 1974, when they entered secondary school, to 1978, when they reached school-leaving age, a cohort of over 6000 schoolchildren from Derbyshire, England, answered a questionnaire about their own and their family's smoking practices and their social activities. Their replies revealed a steady increase in the prevalence of smoking during adolescence. Those children who in 1974 smoked, had friends of the opposite sex, were highly involved in social activities, experienced peer pressure to smoke and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0
5

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 12 publications
3
22
0
5
Order By: Relevance
“…In the present study, these were significant determinants of smoking behaviour. Similar trends have been reported earlier in literature [2,[4][5][6].…”
Section: Methodssupporting
confidence: 91%
“…In the present study, these were significant determinants of smoking behaviour. Similar trends have been reported earlier in literature [2,[4][5][6].…”
Section: Methodssupporting
confidence: 91%
“…Smoking is associated with many other factors, such as smoking among peers and siblings, alcohol intake, drugs, social problems, and personality, and several cohort studies show that having friends who smoke increases the risk that nonsmokers will start to smoke. [23][24][25] As we did not have any information on whether smoking or smoking peers came first, we did not adjust for these variables in the analyses. For the same reasons, we did not include factors such as alcohol consumption, 26 drug abuse, 27 personality, or psychosocial factors, 28 -31 although they are closely associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many children try their first cigarette whilst at primary school (Murray et al, 1984., Swan et al, 1991. This trend in adolescent smoking is particularly important as the majority of adult smokers report initiating smoking before the age of twenty (Charlton, 1992).…”
mentioning
confidence: 99%
“…In Britain there have been five longitudinal studies that have identified elements of the child's social world that are predictive of smoking behaviour (Murray et al, 1984., McNeil et al, 1988., Charlton and Blair, 1989., Gillies and Galt, 1990., and Goddard, 1990). The main factor that predicts smoking is parental smoking, with research showing that children are twice as likely to smoke if their parents smoke (Bewley, 1978., Charlton, 1986., Lader and Matheson, 1991).…”
mentioning
confidence: 99%